Technology and Society: Reflections on the Visions and Tensions of Technology - Santander-Gana, M (UNIV COOPERATIVE COLOMBIA, FAC ENGINEERING, 2015)
Given the difficulty of applauding scientific-technological progress without restriction, the exploration of one or another understanding of technology becomes necessary. The accelerated development and permanent eruption of new technologies, along with the vertiginous renewal of technological artifacts, platforms and systems, pose increasingly greater challenges in the field of decision making. Social changes in the industrialized countries have led certain social collectives to understand that decisions about technology must not be exclusively left to experts and are intrinsically social. In this review article, the implications of technology on society are analyzed; more specifically, the relationship between progress and technology and the difference between technology and technique. Subsequently, the role of technology in society is discussed; the way in which decontextualized use of technology is risky for society and human beings is addressed and the idea of a society able to understand the interweaving between technology and humanity is expressed. Undoubtedly we must ask ourselves certain questions, namely, what could our role be in the creation of this technological future? And what new forms of human identity, political organization, community, and citizen participation arise from the technologies developed?